KEPEMIMPINAN PENDIDIKAN DAN MUTU MADRASAH - Annur, Saipul (Conciencia, 2019)
leaders must be able to work with people they lead to provide motivation to do work sincerely. Thus means education leaders must have feelings. Leaders do not distance themselves from group members with the intention of causing feelings of fear and loyalty, precisely the opposite only by understanding and living the feelings and thoughts of members of the group, someone will be accepted, respected and respected as a leader. In general, the meaning contained in the expression of quality is not new for those involved in general system management thinking and services or specifically the education system. Quality is the key word for the success of competing in business performance, including in the field of education. the most effective efforts by increasing the accountability of the education process. Process accountability is expected to truly be able to guarantee that madrassas can maintain and improve their quality progressively and continuously.